(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
قمنا في هذا البحث بدراسة التفكك الحفزي الهيدروجيني للأوكتان على حفاز الكوبالت المحمّل على الألومينا. أجريت الدراسة عند الدرجة 200oC لما لذلك من أهمية في تفاعل فيشر-تروبش لاصطناع الميتان. بينت الدراسة أن تفكك الأوكتان (قطع الرابطة C-C ) يحدث على أطراف السلسلة لإنتاج الميتان، بينما يكون التفكك في وسط السلسلة ضعيفاً أو مهملاً. تكون سرعة التفاعل خطية عند الضغوط المنخفضة للأوكتان ثم تتغير السرعة بشكل طفيف وهذا يؤكد تغير مرتبة التفاعل، وحيث إن سرعة التفاعل تصل إلى نهاية عظمى ثم تتناقص عند النسب العالية هيدروكربون/هيدروجين. تتناسب انتقائية تشكل الميتان مع تدفق الهيدروجين، وتتناقص بشكل عام انتقائية الهيدروكربونات الناتجة بازدياد نسبة التحول الكلي للأوكتان. The process of Hydrogenolysis of octane over the cobalt catalysts supported on alumina has been studied. The catalytic reaction was carried at 200oC because the important of the Fischer-Tropsch reaction for methane synthesis. This study showed the splitting of C-C bond in octane occurs in the end of the hydrocarbon chain to produce methane, therefore the splitting in the middle of the chain is unless. We note the rate of the reaction was liner at low pressure of octane and then it was changed, and this indicate to changing of the order of the reaction. The rate of the reaction reaches the maximum and then decreases at high ratio of hydrocarbon/hydrogen. The selectivity of methane decreased when the flue of hydrogen increased, and the selectivity of produced hydrocarbon was decreased when the total ratio transforming of the reaction increasing.